Knowledge and attitude towards tele-dentistry among undergraduate dental students in Davanagere city: a cross-sectional survey - Dummi Jaisubash, Veeresh; Yavagal, Puja C.; Vijaykumar, Spandana D.; Ullal, Srinidhi Nayak; Baliga, Vaibhavi R.; Shetty, Varsha Chandrahas; Halamurthy, Vidyashree (International Journal Of Community Medicine And Public Health, 2025)
Background: Knowledge and attitude of undergraduate students towards tele dentistry may influence the use of digital dentistry in the future. To assess the knowledge and attitude towards tele-dentistry among undergraduate dental students in Davanagere City. Methods: A cross-sectional questionnaire survey was conducted in the dental college setting involving a sample of 210 dental undergraduate students in Davanagere city. A pre validated 29 items questionnaire (Cronbach’s coefficient 0.86, Mean Content Validity Ratio (CVR) 0.89) was used to collect data with responses on 3-point Likert Scale Results: The mean age of undergraduate students was 22.36±1.12 years. Around 45.6% of the participants had good knowledge regarding the concept of tele-dentistry and its application in the health sector. The majority of the participants had a favourable attitude towards using tele-dentistry in the future and considered that tele-dentistry could increase the accessibility of the specialists to rural areas and could save time. Conclusions: The undergraduate dental students in Davanagere City had fair knowledge about tele-dentistry and a favourable attitude towards tele-dentistry.